2021
DOI: 10.1155/2021/1866042
|View full text |Cite
|
Sign up to set email alerts
|

Study on Damage Constitutive Model of High-Concentration Cemented Backfill in Coal Mine

Abstract: In order to construct the damage constitutive model (DCM) of high-concentration cemented backfill (HCCB) in coal mine, the generalized Hoek-Brown strength criterion was used as the failure criterion. For the difference of theoretical derivation of constitutive relation, a new DCM based on residual strength was proposed. Combined with the conventional triaxial compression test, the correctness and rationality of the DCM were verified. The damage evolution characteristics of HCCB were analyzed, and the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Yang et al [9] has found the strength of the CGFB solidified body is enough to support the overburden with the help of the surrounding strata when the percentage of fly ash range 15-25% (by weight) while the cement is 5-15 % (by weight) within the CGFB mixture. Yang et al [10] also observed the fly ash improves the rheological behavior of the coal gangue particles suspension, results in the lesser pressure drop and power consumption. However, the excessive fly ash reduction the strength of the CGFB was monitored in the strength tests.…”
Section: Introductionmentioning
confidence: 96%
“…Yang et al [9] has found the strength of the CGFB solidified body is enough to support the overburden with the help of the surrounding strata when the percentage of fly ash range 15-25% (by weight) while the cement is 5-15 % (by weight) within the CGFB mixture. Yang et al [10] also observed the fly ash improves the rheological behavior of the coal gangue particles suspension, results in the lesser pressure drop and power consumption. However, the excessive fly ash reduction the strength of the CGFB was monitored in the strength tests.…”
Section: Introductionmentioning
confidence: 96%